THE POLITICAL IMPACT OF PRESIDENT SOEHARTO'S SPEECH AT THE ABRI LEADERSHIP MEETING ON 27 MARCH 1980: Dampak Politik Pidato Presiden Soeharto pada Rapat Pimpinan ABRI 27 Maret 1980 - Arifin Suryo Nugroho; Dhalia Soetopo; Intan Permana Sari; Ipong Jazimah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research is entitled "The Political Impact of President Soeharto's Speech at the ABRI Leadership Meeting on 27 March 1980."The president's speech at the ABRI Leadership Meeting was used by Soeharto to carry out political control and civil repression against his political opponents.The objectives of this research are: 1) to describe the political situation in Indonesia in the 1980s, 2) to examine the content of President Soeharto's speech delivered on 27 March 1980, and 3) to analyze the political impacts arising from President Soeharto's speech on 27 March 1980. This research is a historical study and employs heuristics, source criticism (verification), external and internal criticism, interpretation, and presentation (historiography). The results of this research indicate that public trust in the government began to decline in 1980. President Soeharto's speech on 27 March 1980 represented an attempt to attack his political opponents. The address also signaled that the Indonesian Armed Forces (ABRI) and Pepabri (Indonesian National Armed Forces) should support Golkar in the election. The speech provoked strong opposition from various elements of society; the most vocal critics were the Petition 50 Group, which issued a Statetement of Concern criticizing President Soeharto.